Genotypic evaluation of sweet pepper in the winter season in Araguari, MG, Brazil - Peixoto, José Ricardo; Ramos, Rogério de Sousa; Júnior, Brasil Faria; Silva, Célio Marcos da; Angelis, Bruno de (Pesquisa Agropecuaria Brasileira, 1999)
An experimental field was carried out in the Jordão farm, located in Araguari, MG, Brazil, at 18o38’30" S and 48o11’18" W, during the winter season, with the purpose of evaluating the agronomic potential of sweet pepper cultivars. The experimental design was in randomized blocks with 17 treatments (17 genotypes) with four replications. The experimental plots were made up each of one line with 30 plants, with 1 m of space between lines and 0,45 m between plants. A total of 10 harvestings were made starting on 28 July 1996 (77 days after transplanting) and ending on November 9, 1996. Several F1 hybrids as Lygia F1, Magali F1, Magali R F1, Acuário F1, Luis F1, Fresco (BS 50-30) F1 and Sambor F1 showed good agronomic characteristics, enabling them to be cultivated in the region, in the winter season. The Lygia F1 cultivar was the highest producer (followed by Acuário F1 e Magali F1) and also showed the highest number of fruits. However, these fruits presented a square shape and fruit classification under the extra AA class. The Acuário F1, Sambor F1, Fresco (BS 50-30) F1, Luis F1 and All Big F1 cultivars produced a high number of fruits extra AA, while Magna Super, Nacional AG-506, Itaipu and Hércules AG-672 showed a high percentage of fruits classified as extra A.